Dinamika Perekonomian Indonesia Sisi Pengeluaran: Sebelum dan Setelah Adanya Covid-19 - Chusnada Choirul Hikmah; Retno Sugiharti (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
The management of fiscal policy in Indonesia will have a positive impact on the market and can provide guarantees for the Indonesian economy. This study aims to determine the effect of PMTB, Household Consumption Expenditure, Government Consumption Expenditure, Indirect Expenditure and Direct Expenditure on GRDP seen from before and before the covid-19 pandemic. This study uses annual data, namely 2019 before the pandemic and 2020 before the pandemic from each province in Indonesia. The method used in this research is the dummy panel method which is processed through a eviews 10 programs for the period 2019 and 2020, the data used is sourced from the Central Statistics Agency and the Ministry of Finance's DJPK from 34 provinces in Indonesia. Based on the results of the study, it can be said that either partially PMTB, household consumption expenditure, government consumption expenditure, indirect expenditure and direct expenditure have a significant effect on GRDP and there is no significant effect between GRDP before the covid-19 pandemic (2019) and after the COVID-19 pandemic. the COVID-19 (2020) pandemic.Keywords: covid-19, economy, expenditure